Alkali-cation-enhanced benzylammonium passivation for efficient and stable perovskite solar cells fabricated through sequential deposition. Issue 37 (11th September 2020) - Cao, Jie; Jiang, Junke; Li, Nan; Dong, Yifan; Jia, Yongheng; Tao, Shuxia; Zhao, Ni
Abstract : Compositional perovskites were developed by a sequential deposition method for highly efficient and stable solar cells. The inclusion of alkali cation and benzylammonium showed synergistic passivation-effect and demonstrated 22.5% efficiency with over 1500 h stability. Abstract : Two-step sequential deposition has been shown to be an effective method to improve the quality of perovskite films and performance of perovskite solar cells (PSCs). In this work, we have developed a two-step sequential deposition method, incorporating an alkali cation ( e.g., Cs + ) and a benzylammonium (BA + ) cation into formamidinium (FA + )-based perovskite thin films for highly efficient and stable PSCs. By combining experimental characterization and theoretical calculations, we demonstrate that not only the co-incorporation of alkali cations and BA + significantly improves the crystallinity and orientational growth of perovskite films, but also Cs + enhances the passivation effect of BA + ions on the perovskite surface via strengthening bonding between BA + and perovskites. In particular, inclusion of Cs + in BA + -passivated perovskites promotes the preferred orientation of defect-free (1 0 0) facets. As a result, we observed remarkable improvements in both open-circuit voltage and fill factor of formamidinium-benzylammonium-cesium (FABACs)-based PSCs, achieving a champion efficiency of 22.5%. More importantly, the FABAC perovskite films demonstrated superior resistance to humidity and photo-thermal stress, and the perovskite-based devices (without encapsulation) retained over 95% of the initial efficiency after exposure to air for 2 months. Manipulating the perovskite composition by combining small alkali and large organic cations in two-step sequential deposition provides an efficient and facile approach to realize highly efficient and stable perovskite devices.